THE IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL WITH STEM (SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATICS) APPROACH TO TRAIN STUDENTS’ SCIENCE PROCESS SKILLS OF XI GRADERS ON CHEMICAL EQUILIBRIUM TOPIC - Nabila Aurelia Awalin; Ismono Ismono (INSECTA: Integrative Science Education and Teaching Activity Journal, 2021)
This study aims to determine the improvement of learning outcomes and students’ science process skills by implementation PBL (Problem Based Learning) model with STEM (Science, Technology, Engineering, Mathematics) based on chemical equilibrium topic. The method in this research is quantitative descriptive with One-Group Pretest-Postest design. The subjects of this study were students of Mathematics and Natural Sciences XI graders in State Senior High School 1 Pulung,  Ponorogo Regency. Data method is; observation, questionnaires, and tests. Technical data analysis used is; analysis of study results data, analysis of observations of learning implementation, analysis of student activities, analysis of learning outcomes completeness, and analysis of student responses. The results in this study were: (1) the mean percentage of the implementation of PBL model based on STEM  in the chemical equilibrium topic was 89.26%; (2) the category of improvement for all indicators of Science Process Skills observing and conclusion that respectively 0.82 and 0.89 are included in the high category, for the skills to formulate problems, formulate hypotheses, determine variables, and analyze data respectively of 0.64 ; 0.42; 0.67; 0.68 and can be categorized as moderate; (3) the learning outcomes of students in the realm of knowledge have increased classically with n-gain of 0.62 in the moderate category; and the last (4) learning by implementation the STEM-based PBL  model on chemical equilibrium material received a positive response from students based on the results of the questionnaire, the percentage was 83%.